Improving Urban Resilience through Green Infrastructure: An Integrated Approach for Connectivity Conservation in the Central City of Shenyang, China. (2nd July 2020) - Liu, Zhimin; Xiu, Chunliang; Ye, Chao
Abstract : Green infrastructure (GI) as an operational physical framework is being increasingly recognized as the most cost-effective way to mitigate and adapt to social-ecological challenges through multifunctional ecosystem services. Conserving the connectivity of GI is conducive to maintaining biodiversity and facilitating ecological processes, which contributes to promote urban resilience and implies that urban governance has made a conscious effort to prepare for uncertainties. Though important, there are few studies on operating GI practically to navigate urban resilience. Based on interdisciplinary knowledge and multiple techniques, this study provides an integrated approach, in which relationships between GI connectivity, resilience potential, and conservation strategies are better addressed. The results indicate that significant changes have taken place in terms of the composition, layout, and connectivity of GI in the central city of Shenyang between 1995 and 2015. Through pinch point identification and barrier detection, conservation strategies by protecting key structures, eliminating local barriers, and implementing differentiated measures according to land use types are therefore proposed. The strategies may be helpful for future policy formulation, planning, and management by rehabilitating a GI network to increase urban social and ecological resilience in the study area and other similar megacities. This integrated approach based on a generic process of geometric analysis has general applicability to make interdisciplinary contributions toward urban resilience.